Knowledge sharing of inpatriates: Empirical evidence from an ability–motivation–opportunity perspective - Schuster, Tassilo; Holtbrügge, Dirk; Engelhard, Franziska (Employee Relations, 2019)
Purpose: The purpose of this study is to analyze the effects of inpatriates’ abilities, motivation and opportunities on knowledge sharing and the moderating role of boundary spanning in this context. Design/methodology/approach: By integrating the ability–motivation–opportunity framework with the concept of boundary spanning four hypotheses are developed, which are tested against the data of 187 inpatriates working in Germany. Findings: The study reveals that inpatriates’ motivation and certain opportunities are positively related to knowledge sharing, whereas inpatriates’ abilities do not show a positive effect. Moreover, it is shown that inpatriate boundary spanning has a moderating effect on this relationship. Originality/value: Based on the results, the study enhances the current literature by introducing the concept of reputation asymmetry. Moreover, requirements of how inpatriates’ assignments should be designed and implications for further research are outlined.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Ability-motivation-opportunity framework; Boundary spanning; Inpatriation; International assignments; Knowledge sharing; Reputation asymmetry